Waiter And Waitress Role In Increasing Service Quality In Jayakarta Hotel : Peranan Waiter Dan Waitress Dalam Meningkatkan Kualitas Pelayanan Di Hotel Jayakarta - Novita Masi Dari Tani MD; Maria Beatrix R. Wellalangi; Maria Flaviana Imakulata (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
This research was conducted to determine the role of waiter and waitress in improving the quality of service at Nat’s Coffee Shop. In this study, method used is a qualitative approach and data collection techniques using interview and observation. In carrying out and optimizing the role and responsibilities of waiter and waitress who are on duty every day, the head waiter divides task to waiter and waitress before the restaurant open to help preparation. The role of the waiter and waitress is the preparation of tableware, responsible for the operaton until the restaurant is closed. Service in Nat’s Coffee Shop based on the 5 dimension are considered adequate, but is not optimal. The obstacles faced by waiter and waiters are the limited number of employess which cause slow service delivery